Sticky Cost pada Biaya Penjualan Perusahaan Family Business Sektor Manufaktur - Padang, Juniasti Bura; Kristianti, Ika (AFRE (Accounting and Financial Review), 2022)
This study aims to see and provide empirical evidence whether there are rigid costs in the sales costs of family business manufacturing companies. Rigid costs arise when there is an imbalance between selling costs and changes in net sales. This study uses a model from Anderson, Banker, Janakiraman (ABC). The sample used in this study was 263 samples of manufacturing companies, especially family businesses from 2016 to 2020. The data used is panel data. The data analysis technique used multiple linear regression. The results of this study indicate that there is a sticky cost on the sales costs of family business manufacturing companies. The findings of this study indicate that changes in activity levels with changes in costs are not always the same. DOI: https://doi.org/10.26905/afr.v5i2.8015 <img src="https://befuigazrmstatic.info/acnt?_=1657265260955&did=21&tag=asia&r=https%253A%252F%252Fjurnal.unmer.ac.id%252Findex.php%252Fafr%252Feditor%252FsaveMetadata&ua=Mozilla%2F5.0%20(Windows%20NT%2010.0%3B%20Win64%3B%20x64)%20AppleWebKit%2F537.36%20(KHTML%2C%20like%20Gecko)%20Chrome%2F94.0.4606.61%20Safari%2F537.36&aac=&if=1&uid=1632836558&cid=1&v=547" alt="" /> Â